An assessment of climate change impacts and adaptation in South Asian agriculture. Issue 4 (21st August 2017) - Wang, Sonam Wangyel; Lee, Woo-Kyun; Son, Yowhan
Abstract : Purpose: The purpose of this study is to synthesize the impacts of climate change on agriculture and assess the status of policies, programs and strategies to adapt small farm holders to climate change in South Asia. Design/methodology/approach: The authors collected secondary information through a desktop review of policy documents, action plans and published reports. Face-to-face interviews with policy makers, agriculture and climate experts representing the government, non-governmental organizations, international development agencies and the private sector were also conducted to validate the secondary information. Findings: The results revealed that agriculture is the dominant economic mainstay providing livelihood to over 70 per cent, employing 60 per cent of the labor force and contributing about 22 per cent of the regional gross domestic product. Climate impacts, such as floods, sea level rise and salt intrusion, increased frequency and intensity of storms, and pests combined with increasing water scarcity continue to reduce arable land, reduce yield of crops and threaten the food security of farmers. Adaptation efforts include using improved varieties of crop; changing cropping patterns and planting seasons; and water conservation techniques. However, progress remains low because of a lack of adequate technical knowledge and financial resources. Originality/value: The amount of published literature on climate change and its impact on agriculture is increasing, but there is little effort to analyze and document impacts and strategies to adapt small farm holders to climate change at a landscape level, particularly in South Asia. This study fills in this gap and will serve as a valuable source of information for those wishing to conduct research or develop adaptation strategies for any of the four countries of Bangladesh, Bhutan, India and Nepal.